Nandrolone decanoate and resistance exercise training favor the occurrence of lesions and activate the inflammatory response in the ventral prostate - Gomes, F. C. [UNESP]; Chuffa, L. G.A. [UNESP]; Scarano, W. R. [UNESP]; Pinheiro, P. F.F. [UNESP]; Fávaro, W. J. [UNESP]; Domeniconi, Raquel Fantin [UNESP] (Wiley, 2016)
Summary: Age is a key factor in the development of prostatic lesions. An increase in reactive oxygen species levels occurs during aging. Furthermore, the indiscriminate use of anabolic androgenic steroids and physical exercise alter the availability of hormones and may promote the appearance of lesions. This study examined whether the use of nandrolone decanoate (ND), associated or not with resistance exercise training, affects the pathways related to the inflammatory response in the ventral prostate of adult and aged rats. Sprague-Dawley rats were distributed into eight experimental groups: sedentary with ND, sedentary without ND, exercise with ND, and exercise without ND. The animals performed resistance exercise training and received ND two times/week (5 mg/kg, i.m.) for 8 weeks. Adult rats were killed immediately following treatment completion, and aged rats remained untreated until reaching 300 days of age. The adult animals that received ND and performed resistance exercise training showed a higher occurrence of lesions with TLR4 activation. Marked IL-6 expression occurred in the group that performed resistance exercise training. The group exposed to ND showed overexpression of TLR2, TLR4, NOX1, Nrf2, TNF-α, and P38MAPK. The animals that received ND and performed training showed increase levels of NFκB, IRF3, IL-6, TNF-α, and NOX1. TLR2 and TLR4 showed no upregulation in the aged animals. The groups exercise + ND showed lesions in the adult stage and after aging, followed by molecular alterations. We concluded that nandrolone decanoate and resistance exercise training can promote the onset of prostatic tumors in the adult stage, and during aging, activating pathways involved in the inflammatory response.
Keywords: Cytokines; Inflammation; Oxidative stress; Physical exercise; Prostate; Steroids